Selling Yourself: A Guide to Writing Effective Resumes - Jonathan F. Wallace; Allen F. Wysocki (EDIS)
This is EDIS document SN 008, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002.